Effect of 30 h sleep deprivation on cycling performance and central fatigue - Temesi, J.; Arnal, P. J.; Verges, S.; Millet, G. Y. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Deterioration in endurance performance with sleep deprivation (SD) has been observed anecdotally and in previous studies (Martin, 1981). Numerous hypotheses have been proposed, including that SD increases perception of effort (RPE). Another effect of SD is the potential for alterations to central motor command during exercise. Although effects on maximal force with SD have not been found, effects of SD on central fatigue are unknown. The aim of this study was to test the hypothesis that increased supraspinal fatigue contributes to impaired exercise performance with SD. Methods: 9 active males with normal sleep patterns performed 2 randomized and counterbalanced 2-day sessions. On day 1 (J1), subjects performed neuromuscular tests comprising maximal (MVC) and submaximal voluntary contractions of knee extensors with peripheral nerve (PNS) and transcranial magnetic stimulation. On day 2 (J2), after a night of complete SD or normal sleep (CO), subjects performed tests as per J1 before, after cycling 40 min at 65% maximal aerobic power (MAP) and then after cycling to exhaustion (65% MAP; + 5% MAP every 5 min). MVC, voluntary activation (VA), maximal M-wave at rest (Mmax) and during MVC (Msup), motor evoked potential (MEP) and potentiated twitch (TwPot) amplitudes, RPE and performance time were analyzed by repeated-measures ANOVA or t-test with significance at 0.05. Results: No differences were observed between SD and CO or between J1 and J2 before cycling (p>0.05). On J2, RPE increased and MVC decreased with cycling time (both p<0.001). This was paralleled by the appearance of low-frequency fatigue (p<0.001) and decreasing TwPot (p<0.001) and %VA PNS (p=0.04). Vastus lateralis (VL) MEP/Mmax at 50, 75 and 100% MVC increased in amplitude with time on J2 (P<0.05). There were no differences in MEP/Mmax amplitudes in Rectus femoris or Vastus medialis, nor for MEP/Msup in any quadriceps muscle. Both Mmax and Msup amplitudes decreased in all quadriceps muscles with time on J2 (p<0.05). Discussion: The results of this study showed no change in neuromuscular measures with SD. Endurance cycling to exhaustion produced a decrease in maximal force associated with low frequency fatigue and some central fatigue. At fatigue, cortical excitability was elevated in VL. These effects were not, however, accentuated with SD. Although exercise time to exhaustion with SD was 3.5% shorter than CO, this difference was not significant. Evidence of increased RPE and central fatigue, especially increased supraspinal fatigue, with SD were not observed, perhaps explaining the lack of performance difference between the two conditions